'Chapter 10: 5G-enabled IoT applications in healthcare: Transforming the Industry 5.0 healthcare landscape' in "1st Edition, The Future of Human-Computer Integration Industry 5.0 Technology, Tools, and Algorithms, Edited By Norliza Katuk, Roberto Vergallo, Tito Sugiharto, Copyright 2024". - Mohamad Nazim, Jambli; Mohamad Zul Haziq, Mohd Fadzli; Sinarwati, Mohamad Suhaili; Nur Haryani, Zakaria (CRC Press, 2024)
The Future of Human-Computer Integration: Industry 5.0 Technology, Tools, and Algorithms provides a valuable insight into how Industry 5.0 technologies, tools, and algorithms can revolutionise industries and drive innovation.